Creative Thinking of Chemistry and Chemistry Education Students in Biochemistry Learning through Problem Based Learning with Scaffolding Strategy - Ernawati, M. D. W.; Sudarmin, S.; Asrial, A.; Muhammad, D.; Haryanto, H. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This study aimed to describe students' creative thinking skills in a problem-based learning model with scaffolding in the Biochemistry course. This is mixed-method research with an explanatory sequential research design with a sample of 173 students from the Chemistry Education and Chemistry study programs, Universitas Jambi. In this study, the researchers only used the experimental class. The sampling technique used is total sampling and purposive sampling. Data were collected using observation sheets, test instruments, interview instruments, and response questionnaires. Quantitative data analysis used is hypothesis testing in the form of ANOVA test with Post-Hoc Scheffe test and T-test. The findings of this study indicate that the ANOVA test results showed a significant difference in the average creative thinking (cognitive) test results and student response questionnaire results in scaffolding-based integrated biochemistry learning. In addition, there is also a significant effect between cognitive test results on student responses in scaffolding-based integrated biochemistry learning. So it can be concluded that there are differences in the creative thinking skills of chemistry education students and chemistry students in using scaffolding integrated problem-based learning models in Biochemistry courses.